Enzyme-linked immunosorbent assay for post-slaughter diagnosis of bovine leukosis - A. R. Mustafayev; M. O. Baratov (Ветеринария сегодня)
Postmortem diagnosis of enzootic bovine leukosis is made on the basis of the results of tests of biological materials from emergently slaughtered or fallen animals using pathomorphological, histological and molecular genetic methods that have some disadvantages. Results of post-slaughter diagnostic tests for bovine leukosis with enzyme-linked immunosorbent assay are described in the paper. For this purpose, 83 swabs were collected from different carcass parts including 71 swabs from carcasses of the animals that were not pre-slaughter tested and 12 samples from the carcasses of the animals that were pre-slaughter tested with immunodiffusion assay and found bovine leukemia virus-seronegative (control samples). Sterile scalpels, cotton wool, 5 mL tubes with caps were used for swab collection. The samples were taken from incisions in carcasses and internal organs of slaughtered animals with sterile cotton-wool swabs and placed in single-use tubes. Distilled water (or isotonic solution – 0.85% NaCl) was added to the tubes with samples, 0.1 to 0.2 mL per tube depending on the sample size, and the tubes were left at room temperature (22–26 °С) for 1.5–2.0 hours and regularly shaken. Resulting homogeneous substrate was used for enzyme-linked immunosorbent assay carried out in accordance with the instructions for the test-kit for detection of antibodies against bovine leukemia virus. Specific antibodies to bovine leukemia virus gp51 antigen were detected in 6 (8.5%) out of 71 swabs subjected to the laboratory tests. Therewith, the antibodies were detected only in 3 swabs (4.2%) when the swabs were tested with immunodiffusion assay. All 12 control samples from animals that were pre-slaughter tested and found seronegative were negative when tested with enzyme-linked immunosorbent assay. Therefore, the above-said serological method can be used for post-slaughter diagnosis of bovine leukosis together with conventional methods.